Time Travel Twins: The Viking Attack - Josh Lacey (Andersen Press, 2023)
Twins, Scarlett and Thomas, are studying the Vikings and Anglo-Saxons at school and they have a homework project to do. When Thomas is struggling for inspiration, Grandad comes to the rescue with his time machine. Thomas is catapulted onto a Viking long ship and it$1 (Bs not long before he$1 (Bs being told oral tales, fitted out with armour and weapons and is getting ready to attack a Saxon village. But uh oh, his sister Scarlett has landed in a Saxon village, in a pile of pig poo to be exact. Things seems to be getting better when she befriends the young Alfred the Great, but watch out, Scarlett, there$1 (Bs a Viking ship on its way.s
Keywords: Adventure -- Adventure